2017
DOI: 10.1140/epjc/s10052-017-4597-z
|View full text |Cite
|
Sign up to set email alerts
|

Stability of the Einstein static universe in f(R, T) gravity

Abstract: The Einstein static (ES) universe has played a major role in various emergent scenarios recently proposed in order to cure the problem of the initial singularity of the standard model of cosmology. In the model we address, we study the existence and stability of an ES universe in the context of f (R, T ) modified theories of gravity. Considering specific forms of the f (R, T ) function, we seek for the existence of solutions representing ES state. Using dynamical system techniques along with numerical analysis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
77
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 135 publications
(78 citation statements)
references
References 162 publications
(172 reference statements)
1
77
0
Order By: Relevance
“…It has been studied in several astrophysical and cosmological aspects, by assuming different choices for the arbitrary function of R and T ; see [12][13][14], for instance.…”
Section: Introductionmentioning
confidence: 99%
“…It has been studied in several astrophysical and cosmological aspects, by assuming different choices for the arbitrary function of R and T ; see [12][13][14], for instance.…”
Section: Introductionmentioning
confidence: 99%
“…In GR, this was reconsidered, and it was found that the Einstein static universe can be stable against small inhomogeneous vector and tensor perturbations as well as adiabatic scalar density perturbations if the universe contains a perfect fluid with w = c 2 s > 1/5 [25,26,31]. Of course, the stability of the Einstein static universe has also been extensively studied in many modified gravities, for example, loop quantum cosmology [32], f (R) theory [33][34][35], f (T ) theory [36,37], modified Gauss-Bonnet gravity [38,39], Brans-Dicke theory [40][41][42][43], Horava-Lifshitz theory [44][45][46], massive gravity [47,48], braneworld scenario [49][50][51], Einstein-Cartan theory [52], f (R, T ) gravity [53], hybrid metric-Palatini gravity [54] and so on [55][56][57][58][59][60][61][62]. We refer to e.g.…”
Section: Introductionmentioning
confidence: 99%
“…to t. Taking f (R, T ) = R + αR 2 + 2λT and using Eqs. (7), (18), (19) in Eq. (15), we get the following field equations…”
Section: Cosmological Dynamics Of the Universementioning
confidence: 99%